Una Adaptación del Protocolo EDCA para Tiempo Real - Alimenti, Omar; Friedrich, Guillermo; Reggiani, Guillermo; Tonietti, Santiago; Maidana, Federico; de Marco, Dami'n (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2011)
A network control system (NCS) on wireless networks (WNCS) presents problems of reliability and timing own of radio channel and the mechanisms of media access control (MAC) that cause unpredictable latency and packet loss. The EDCA (Enhanced Distributed Channel Access) MAC, of the 802.11e, provides four differentiated levels of Quality of Service (QoS) that do not guarantee a bounded delay for sending packets. This paper proposes to properly handle the contention window (CW), the backoff counter and arbitration inter-frame spaces (AIFS) of EDCA, to limit transmission latency and to avoid packet loss.